Studi Literatur: Pengaruh Pembelajaran Berbasis Proyek terhadap Kreativitas dan Hasil Belajar Siswa SMP dalam Mata Pelajaran IPA - Nur Aisah (International Forum of Researchers and Lecturers, 2024)
The study focuses on how junior high school (SMP) science students' creativity and learning outcomes are affected by project-based learning (PjBL). The goal of the study is to improve knowledge of how PjBL can affect the creativity and learning outcomes of junior high school science students. Promoting Student Involvement: PjBL is anticipated to boost student involvement in the educational process, which in turn facilitates more profound and significant learning. A qualitative approach was taken, and the literature review served as the mechanism for gathering data. This study intends to aid in the creation of more efficient teaching methods through a thorough selection of relevant material and methodical analysis techniques. The findings demonstrate that students' creativity and learning outcomes in scientific courses are significantly enhanced by project-based learning. PjBL teaches students how to use their knowledge in practical contexts in addition to helping them retain information. Therefore, it is anticipated that this research will offer insightful information to educators and policymakers in order to develop more innovative and successful teaching methods in classrooms.